Contrasting responses of above- and belowground diversity to multiple components of land-use intensity - Gaëtane Le Provost (Nature Portfolio, 2021)
Land use intensification is a major driver of biodiversity change. Here the authors measure diversity across multiple trophic levels in agricultural grassland landscapes of varying management, finding decoupled responses of above- and belowground taxa to local factors and a strong impact of landscape-level land use.